MATEMÁTICAS B 4º ESO

Curso 2009-10

ÁLGEBRA

SOLUCIÓN EJERCICIOS OBLIGATORIOS TEMA 4
MATEMÁTICAS B 4º ESO A
7b) log 3 27 = x ⇒ 3 x = 27 ⇒ x = 3
1
1
=3⇒x =
x
3
2
2
h) log 2 x 4 = 2 ⇒ (2 x) = 4 ⇒ 4 x = 4 ⇒ x 2 = 1⇒ x = ±1⇒ x = 1

e) log x 3 = −1⇒ x −1 = 3 ⇒
⎛ 1⎞
k) log 1 x = −3 ⇒ ⎜ ⎟
⎝3⎠
3

−3

= x ⇒ x = 3 3 = 27

81
1
− log 2 8 2 =
4
3
13
4
1
1
1
1
= log 2 16 − 2 − log 2 8 = ⋅ 4 − 2 − ⋅ 3 = − 2 − = −
2
6
3
2
3
2
3
1
1
g) log
− log1+ log 3
= −2 − 0 − 4 = −6
100
81
)
1
1
3
i) log 3
− log 3 0'3 = log 3 − log 3 = −2 − (−1) = −1
3
9
27
1
1
k) log 2 8 − log 2 8 3 = log
− 3 log 2 8 = −8 − 3 ⋅ 3 = −8 − 9 = −17
32
2 256

e) log 2 3 16 + log 2 0'25 − log 2 8 = log 2 16

1
3

+ log 2

9e)
log 3 27N − log 2 M 2 = log 3 (27N)

=

1
2

− log 2 M ⋅ 2

1
2

=

1
1
log 3 27N − (log2 M + log 2 2 2 ) =
2

1
1
1
1 3 q
1
q
(log3 27 + log 3 N) − log 2 M − log 2 2 = (3 + q) − p − = + − p − = 1+ − p
2 2 2
2
2
2
2
2

2 log 3

= 2q −

log 2

3

g)
N
3

9

+ log 2

1
1
1024
= 2(log3 N − log 3 9 3 ) + log 2 1024 − log 2 M = 2(q − ⋅ 2) + 10 − p =
3
M

26
4
+ 10 − p = 2q −
−p
3
3
i)
M4
8

= log 2 M

4

3

− log 2 8

1
2

=

4
1
4p 3
⋅p − ⋅ 3 =

3
2
3 2

1

MATEMÁTICAS B 4º ESO Curso 2009-10 ÁLGEBRA 10b) log7 4 = 11log f) 3 x + 1 − log 3x + 1 ⇒ log 2x − 3 log 4 = 0'71 log 7 e) log 3 10 = 2 x − 3 = 1 − log 5 ⇒ log ⋅ 5 = 1⇒ 101 = 5 = 3 x + 1⇒ 5x = 13 ⇒ x = 3x + 1 2x − 3 ⇒2= 3 x + 1 − log log10 = 2'1 log 3 2 x − 3 + log 5 = 1 ⇒ 3x + 1 3x + 1 ⇒4= ⇒ 8 x − 12 = 2x − 3 2x − 3 13 5 h) 2 2 (x − 4 x + 7) ⋅ log 5 + log16 = 4 ⇒ log 5 x −4 x +7 + log16 = 4 ⇒ log 5 x −4 x +7 ⋅ 16 = 4 ⇒ 2 2 2 2 10000 ⇒ 10 4 = 5 x −4 x +7 ⋅ 16 ⇒ = 5 x −4 x +7 ⇒ 625 = 5 x −4 x +7 ⇒ 5 4 = 5 x −4 x +7 ⇒ 16 4 ± 16 − 4 ⋅ 3 4 ± 2 ⇒ 4 = x 2 − 4x + 7 ⇒ x 2 − 4x + 3 = 0 ⇒ x = = ⇒ x 1 = 3. x 2 = −4 2 2 12i) 31 31 5 x =a 31 ⇒ 5 x + 5 x ⋅ 51 + 5 x ⋅ 5 2 = ⎯⎯⎯→ a + 5a + 25a = ⇒ 25 25 25 31 1 ⇒ 31a = ⇒a= = 5 x ⇒ x = −2 25 25 5 x + 5 x +1 + 5 x + 2 = 2 . x 2 = 1 2 2 i) 2 5 2 x 32 32 x ⎛x⎞ ⎛x⎞ 5 log + 2 log = 3 log x − log ⇒ log⎜ ⎟ + log⎜ ⎟ = log x 3 − log ⇒ 2 3 9 9 ⎝3⎠ ⎝2⎠ ⇒ log x5 x2 x3 x7 9x 3 ⋅ = log ⇒ = ⇒ 32 x 7 = 2592x 3 ⇒ x 3 (32 x 4 − 2592) = 0 ⇒ 32 32 9 288 32 9 ⇒ x 3 = 0 ⇒ x1 = 0 ⇒ 32 x 4 − 2592 = 0 ⇒ x 4 = Sólo vale x=3 2592 = 81⇒ x = ± 4 81 = ±3 32 l) log x 2 (8 − 2 x) = 1⇒ (x 2 )1 = 8 − 2 x ⇒ x 2 + 2 x − 8 = 0 ⇒ x = = − 2 ± 4 − 4 ⋅ (−8) = 2 − 2 ± 4 + 32 − 2 ± 6 = ⇒ x 1 = 2.

⇒ a2 = 2 = 2 x ⇒ x = 1 u) 7 x =a 2 x +3 7 − 8 ⋅ 7 x +1 + 1 = 0 ⇒ 7 2 x ⋅ 7 3 − 8 ⋅ 7 x ⋅ 71 + 1 = 0 ⎯⎯ ⎯→ 343a − 56a + 1 = 0 ⇒ 56 ± 3136 − 4 ⋅ 343 56 ± 42 ⇒a= = ⇒ 686 686 98 1 ⇒ a1 = = = 7 x ⇒ x = −1 686 7 14 1 ⇒ a2 = = = 7 x ⇒ x = −2 686 49 w) 3 2 x −1 3 = 9 1 x − 4 2 x2 − ⇒3 2 x −1 =9 3 1 4 ⇒3 2 x −1 =3 1⎞ ⎛ 2⎜ x 2 − ⎟ 4⎠ ⎝ 3 ⇒ 2x − 1 = 2x 2 − 2 ⇒ 8x − 4 = 8x 2 − 2 ⇒ 4 .MATEMÁTICAS B 4º ESO Curso 2009-10 ÁLGEBRA k) 2 2x a2 2 x =a 2 = 24 ⎯ ⎯ ⎯ → a + = 24 ⇒ 2a 2 + a 2 = 48 ⇒ 1 2 2 ⇒ 3a2 = 48 ⇒ a2 = 16 ⇒ a = ±4 = 2 x ⇒ x = 2 m) 4 x =a 2 x +1 − 4 x + 2 = 768 ⇒ 4 2 x ⋅ 41 − 4 x ⋅ 4 2 = 768 ⎯⎯ ⎯→ 4a 2 − 16a − 768 = 0 ⇒ 4 16 ± 256 − 4 ⋅ 4 ⋅ (−768) 16 ± 256 + 12288 16 ± 112 ⇒a= = = ⇒ 8 8 8 ⇒ a1 = 16 = 4 x ⇒ x = 2 4 x + 2 2 x −1 = 24 ⇒ 2 2 x + ⇒ a 2 = −12 ≠ 4 x o) 3x a 3 x =a x x 1 + 3 + 3 ⋅ 3 = 117 ⎯ ⎯ ⎯→ + a + 3a = 117 ⇒ 1 3 3 x ⇒ a + 3a + 9a = 351⇒ 13a = 351⇒ a = 27 = 3 ⇒ x = 3 q) 5 52 5 x =a 5 x − x −1 + 24 = 0 ⇒ 5 x − 51−(x −1) + 24 = 0 ⇒ 5 x − 5 2− x + 24 = 0 ⇒ 5 x − x + 24 = 0 ⎯⎯ ⎯→ 5 5 − 24 ± 576 − 4 ⋅ (−25) − 24 ± 26 25 → a− + 24 = 0 ⇒ a 2 − 25 + 24a = 0 ⇒ a = = ⇒ a 2 2 3 x −1 + 3 x + 3 x +1 = 117 ⇒ ⇒ a1 = 1 = 5 x ⇒ x = 0 ⇒ a 2 = −25 ≠ 5 x s) x+3 2 x =a x 4 − 2 + 12 = 0 ⇒ (2 x )2 − 2 x ⋅ 2 3 + 12 = 0 ⎯⎯ ⎯→ a 2 − 8a + 12 = 0 ⇒ ⇒a= 8 ± 64 − 4 ⋅ 12 8 ± 4 log 6 = ⇒ a1 = 6 = 2 x ⇒ log 6 = x log 2 ⇒ x = = 2'58 2 2 log 2 Κ Κ Κ Κ Κ Κ Κ Κ Κ Κ Κ Κ Κ .

MATEMÁTICAS B 4º ESO Curso 2009-10 ⇒ 8x 2 − 8x + 2 = 0 ⇒ x = y) ÁLGEBRA 8 ± 64 − 64 1 = 16 2 2x a 2 x =a 2 + 2 + 2 = 7 ⇒ 1 + 2 x + 2 x ⋅ 21 = 7 ⎯⎯ ⎯→ + a + 2a = 7 ⇒ a + 2a + 4a = 14 ⇒ 2 2 x ⇒ 7a = 14 ⇒ a = 2 = 2 ⇒ x = 1 aa) 3 x =a 2 x +1 3 − 14 ⋅ 3 x +1 + 135 = 0 ⇒ 3 2 x ⋅ 31 − 14 ⋅ 3 x ⋅ 31 + 135 = 0 ⎯⎯ ⎯→ 3a 2 − 42a + 135 = 0 ⇒ 42 ± 1764 − 1620 42 ± 12 ⇒a= = ⇒ 6 6 ⇒ a1 = 9 = 3 x ⇒ x = 2 x −1 x x +1 ⇒ a 2 = 5 = 3 x ⇒ log 5 = x log 3 ⇒ x = log 5 = 1'46 log 3 4 .

Sign up to vote on this title
UsefulNot useful